Dermal Fibroblast Migration and Proliferation Upon Wounding or Lipopolysaccharide Exposure is Mediated by Stathmin - Cen, Ruiyan; Wang, Liqun; He, Yongqing; Yue, Chenda; Tan, Yang; Li, Lingfei; Lei, Xia (Frontiers in Pharmacology, 2022)
The dermal fibroblast is a crucial executor involved in wound healing, and lipopolysaccharide is a key factor in initiating the migration and proliferation of the dermal fibroblasts, followed by wound healing. However, the underlying molecular mechanism is still unknown. In this study, we demonstrated that stathmin increased concomitantly with p38/MAPK pathway activation by lipopolysaccharide stimulation of the human dermal fibroblast (HDF), which induced microtubule (MT) depolymerization followed by increased HDF migration and proliferation. In contrast, the application of taxol, the small interfering RNA transfection of stathmin, or the application of the p38/MAPK inhibitor SB203580 suppressed MT depolymerization and HDF migration and proliferation. Additionally, the overexpression of a MKK6(Glu) mutant, which constitutively activated p38/MAPK, resulted in MT depolymerization and, subsequently, promoted HDF migration and proliferation. Our data reveal a crucial role of stathmin in HDF migration and proliferation. These findings will provide new targets and strategies for clinical interventions in wound healing.